Osteoblast compatibility of 3D printed Co–Cr–Mo alloys with different building direction. Issue 2 (18th June 2019) - Migita, Satoshi; Sakashita, Kosuke; Suyalatu,
Abstract : Three‐dimensional (3D) metal printing is an attractive technique for fabricating biomedical devices. The microstructures and mechanical properties of the fabricated 3D metal printed products show anisotropy because the grains grow along the z ‐axis direction. However, the effects of different printing directions on the cytocompatibility of the products are unknown. In the present study, cobalt–chromium–molybdenum (Co–Cr–Mo) alloy cylinders were fabricated along the z ‐axis (vertical) and x ‐axis (horizontal), respectively, and the effect of build direction on the cytocompatibility was evaluated. The build direction of 3D printed Co–Cr–Mo alloy changed grain anisotropy; however, there was no statistical difference in grain size. The wettability, protein adsorption, cell attachment, and cell proliferation on the disks of vertical and horizontal products were similar to those on cast alloy; they were significantly lower than those of commercially pure titanium and tissue culture polystyrene. The build direction of 3D printed Co–Cr–Mo alloy does not affect osteoblast compatibility.